Personal Branding for University Graduates: A Literature Review - Nthabeleng Rammile (Journal of World Economy, 2025)
Increasing competition in the world of work continues to heighten the importance of personal branding for graduates and their career development. Personal branding initially emerged as a marketing concept and evolved over time to become a tool that graduates can now use as a strategy for the presentation of skills, identity, values and career goals. This literature review observes the relationship between personal branding and graduate employability. Emerging themes over the past decade are observed. Specifically: the definition and evolution of personal branding, its connection to employability outcomes, the influence of digital presence, the role of authenticity and self-concept, institutional support, and the critiques surrounding personal branding as an ideological construct. A key challenge that remains is one of ensuring that introverted and marginalised graduates are not forced to conform to extroverted norms. While Universities are slowly acknowledging the role of personal branding, its integration into curricula and career services remains a challenge. It is therefore encouraged that future research needs to focus on coming up with inclusive, ethical, and authentic strategies. Such strategies should consider psychological and social impact while assisting graduates to package their personal brands successfully.